Medium density fiberboard made from kenaf (Hibiscus cannabinus L.) stem: effect of thermo-mechanical refining and resin content - Nayeri, Majid Dehghan; Md Tahir, Paridah; Jawaid, Mohammad; Ashaari, Zaidon; Abdullah, Luqman Chuah; Bakar, Edi Suhaimi; Namvar, Farideh (North Carolina State University, 2014)
The present study deals with the physical and mechanical properties of dry-formed medium density fibreboard (MDF) made from renewable biomass kenaf (Hibiscus cannabinus L.) stem as a function of adhesive level and refining conditions. Raw material was prepared by heating for 5 min at pressure levels of 6 and 8 bars. Experimental samples with a target density of 700 kgm-3 were produced with 10, 12, or 14% urea formaldehyde as a binder. Physical properties of MDF panels, such as thickness swelling (TS) and water absorption (WA) as well as mechanical properties including modulus of rupture (MOR), modulus of elasticity (MOE), and internal bonding (IB), were evaluated. Based on the test results, resin content and refining pressure have significant effects on the physical and mechanical properties of MDF panels. High resin content and pressure produced MDF boards with low WA and TS but high MOR, MOE, and IB. At 8 bars pressure and 14% resin content, the MDF recorded optimum WA (83.12%), TS (20.2%), MOR (25.3 MPa), MOE (3450 MPa), and IB (0.51 MPa).